2014
DOI: 10.1177/0193841x14550863
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Complexities of Qualitative Comparative Analysis

Abstract: QCA carries great potential for scholars in evaluation and directly neighboring areas interested in the analysis of complex dependencies in configurational data. If users beware of the pitfalls introduced in this article, and if they avoid mechanistic adherence to doubtful "standards of good practice" at this stage of development, then research with QCA will gain in quality, as a result of which a more solid foundation for cumulative knowledge generation and well-informed policy decisions will also be created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…[28,29]). In this connection, our argument also updates [30] and [31] insofar as we hold that it is the objective function given to an optimization algorithm, not the algorithm per se, that may induce bias.…”
Section: Qca: Foundations Diffusion Analytical Approachmentioning
confidence: 99%
“…[28,29]). In this connection, our argument also updates [30] and [31] insofar as we hold that it is the objective function given to an optimization algorithm, not the algorithm per se, that may induce bias.…”
Section: Qca: Foundations Diffusion Analytical Approachmentioning
confidence: 99%
“…4.It is not clear why the authors argue that “csQCA aims to develop explanatory models on the basis of a systematic comparison of a limited number of cases ( N < 100)” (p. 104), but then carry out simulations for up to 300 cases. We would argue that QCA works with any number of cases (see Thiem 2014:491–92).…”
mentioning
confidence: 99%
“…Finally, this study selects the 'standard analysis' option over the 'specify analysis,' as suggested in the literature (Thiem, 2014;Baumgartner & Thiem, 2017). Due to the required limited diversity for a neat solution, QCA introduces the Quine-McCluskey algorithm to logically reduce redundancies based on minimal disjunctions in solution models when applying the 'specify analysis' option (Ragin, 2008).…”
Section: Analysis Of Sufficient Conditionsmentioning
confidence: 99%